Partial asynchrony of coniferous forest carbon sources and sinks at the intra-annual time scale - Silvestro, Roberto; Mencuccini, Maurizio; García-Valdés, Raúl; Antonucci, Serena; Arzac, Alberto; Biondi, Franco; Buttò, Valentina; Camarero, J Julio; Campelo, Filipe; Cochard, Hervé; Čufar, Katarina; Cuny, Henri E; et al. (Nature communications, 2024)
As major terrestrial carbon sinks, forests play an important role in mitigating climate change. The relationship between the seasonal uptake of carbon and its allocation to woody biomass remains poorly understood, leaving a significant gap in our capacity to predict carbon sequestration by forests. Here, we compare the intra-annual dynamics of carbon fluxes and wood formation across the Northern hemisphere, from carbon assimilation and the formation of non-structural carbon compounds to their incorporation in woody tissues. We show temporally coupled seasonal peaks of carbon assimilation (GPP) and wood cell differentiation, while the two processes are substantially decoupled during off-peak periods. Peaks of cambial activity occur substantially earlier compared to GPP, suggesting the buffer role of non-structural carbohydrates between the processes of carbon assimilation and allocation to wood. Our findings suggest that high-resolution seasonal data of ecosystem carbon fluxes, wood formation and the associated physiological processes may reduce uncertainties in carbon source-sink relationships at different spatial scales, from stand to ecosystem levels.
Keywords: Tracheophyta; Trees; Carbon Sequestration; Forests; dřevo; Ecosystem; Wood; lesy; stromy; Carbon Cycle; sekvestrace uhlíku; cévnaté rostliny; biomasa; klimatické změny; Carbon; roční období; Climate Change; Seasons; koloběh uhlíku; Biomass; uhlík; ekosystém